Microcontroller-Based Kurdish Understandable and Readable Digital Smart Clock - Hama Rawf, Karwan Mahdi; Abdulrahman, Ayub Othman (Science Journal of University of Zakho, 2022)
A smart clock is any digital clock that has at least one intelligent feature. Moreover, it provides time with synchronizing automatically base on the standard measurement, which is determined during the implementation software on the hardware architecture design. This study presents an efficient cost-effective smartwatch for disable people based on the Atmega328p microcontroller (Arduino Uno) that is programmed in “Arduino” (C based) programming language. Moreover, the system uses DS1302 real time clock, SD card memory, push button, voice recognition module, liquid crystal display (LCD), and sound speaker. The clock sounds time in Kurdish language when a related switch is pressed or asked via microphone, it also shows the time on LCD. Finally, the system is applied successfully with a satisfactory cost and performance for the proposed application according to the achieved test results.
Keywords: Smart Watch; Wearable system; Kurdish Sound Recognition; Liquid Crystal Display; Microcontroller; “Arduino” (C based) programming